The Expression and Roles of the Super Elongation Complex in Mouse Cochlear Lgr5+ Progenitor Cells - Chen, Yin; Qiang, Ruiying; Zhang, Yuan; Cao, Wei; Wu, Leilei; Jiang, Pei; Ai, Jingru; Ma, Xiangyu; Dong, Ying; Gao, Xia; Li, He; Lu, Ling; et al. (Frontiers in Cellular Neuroscience, 2021)
The super elongation complex (SEC) has been reported to play a key role in the proliferation and differentiation of mouse embryonic stem cells. However, the expression pattern and function of the SEC in the inner ear has not been investigated. Here, we studied the inner ear expression pattern of three key SEC components, AFF1, AFF4 and ELL3, and found that these three proteins are all expressed in both cochlear hair cells and supporting cells. We also cultured Lgr5+ inner ear progenitors in vitro for sphere-forming assays and differentiation assays in the presence of the SEC inhibitor flavopiridol. We found that flavopiridol treatment decreased the proliferation ability of Lgr5+ progenitors, while the differentiation ability of Lgr5+ progenitors was not affected. Our results suggest that the SEC might play important roles in regulating inner ear progenitors and thus regulating hair cell regeneration. Therefore, it will be very meaningful to further investigate the detailed roles of the SEC signaling pathway in the inner ear in vivo in order to develop effective treatments for sensorineural hearing loss.